Impact of antiplatelet therapy on outcomes of sepsis: A systematic review and meta-analysis. - Xufang Wang; Huifei Zhou (PLoS ONE)
Objective Antiplatelet therapy has been studied for its potential benefits in various cardiovascular conditions, but its role in sepsis remains less clear. This review aims to systematically analyse the available evidence on the effects of antiplatelet therapy in sepsis to assess its potential benefits and risks. Material and methods The studies published until 01st April 2024 from PubMed, Embase and Scopus databases were searched. Pooled effect sizes were reported as relative risks (RR) or weighted mean difference (WMD) with corresponding 95% confidence intervals (CI). Outcomes included mortality, length of intensive care unit (ICU) stay, hospital stay, and the risk of complications. The certainty of evidence was evaluated using GRADE. Results Twenty-one studies were included. Antiplatelet therapy was associated with significantly lower risk of in-hospital mortality (RR 0.76, 95% CI: 0.67, 0.87), and mortality at one (RR 0.77, 95% CI: 0.66, 0.90) and three months (RR 0.77, 95% CI: 0.66, 0.90) follow up. Risk of complications was comparable in all patients (RR 1.01, 95% CI: 0.84, 1.21). ICU stay (in days) (WMD -0.23, 95% CI: -0.53, 0.07; N=7, I2=97.2%) and overall duration of hospital stay (in days) (WMD 0.63, 95% CI: -0.66, 1.92; N=6, I2=93.2%) was also statistically similar among patients who received and did not receive antiplatelet drugs. The certainty of evidence for the outcomes ranged from "low to very low". Conclusion Antiplatelet therapy appears safe and significantly lowers the risk of short-term mortality in septic patients. While antiplatelet therapy did not impact the duration of ICU or overall hospital stay, our findings underscore the potential of antiplatelet agents as a beneficial adjunctive therapy in sepsis management.